Comparison of Outcomes of Enucleation vs. Standard Surgical Resection for Pancreatic Neoplasms: A Systematic Review and Meta-Analysis - Shen, Xiaoying; Yang, Xiaomao (Frontiers in Surgery, 2022)
Background: With advancement in health technology, the detection rate of pancreatic neoplasms is increasing. Tissue sparing surgery (enucleation) as well as standard surgical resection are two commonly used modalities of management. There are studies comparing clinical outcomes between these two modalities; however, there is lack of studies that systematically pool the available findings to present conclusive and reliable evidence. Methods: A systematic search was conducted using the PubMed, Scopus, and Google Scholar databases. Studies that were randomized controlled trials or cohort based or analysed retrospective data were considered for inclusion. Studies should have been done in adult patients with pancreatic neoplasms and should have examined the outcomes of interest by the two management modalities i.e., enucleation and standard surgical resection. Statistical analysis was performed using STATA software. Results: A total of 20 studies were included in the meta-analysis. The operation time (in minutes) (WMD -78.20; 95% CI: -89.47, -66.93) and blood loss (in ml) (WMD -204.30; 95% CI: -281.70, -126.90) for enucleation was significantly lesser than standard surgical resection. The risk of endocrine (RR 0.32; 95% CI: 0.18, 0.56) and exocrine insufficiency (RR 0.16; 95% CI: 0.07, 0.34) was lower whereas the risk of postoperative pancreatic fistula (RR 1.46; 95% CI: 1.22, 1.75) was higher in enucleation, compared to standard surgical resection group. There were no differences in the risk of reoperation, readmission, recurrence, mortality within 90 days and 5-years overall mortality between the two groups. Conclusions: Enucleation, compared to standard surgical resection, was associated with better clinical outcomes and therefore, could be considered for selected pancreatic neoplasms. There is a need for randomized controlled trials to document the efficacy of these two management techniques.